PELAKSANAAN PEMBELAJARAN DI SEKOLAH PADA MASA KEBIASAAN BARU - Husaini Husaini (ADIBA : JOURNAL OF EDUCATION, 2021)
At this time the covid-19 virus made many parties think harder about how to carry out the learning process for children and the future of the nation, therefore the Ministry of Education and Culture and the local government to make various efforts to adjust changes in new habits to become the most frequently spoken words today. This is none other than due to the corona virus outbreak which is a frightening specter for the entire world. make and force everyone to have the courage to adapt and live side by side with this very scary Corona Virus disease outbreak. And although the case cannot be said to be under control, relaxation which is the transitional stage after the large-scale easing of social restrictions (PSBB) is the most reasonable choice at this time. The health and safety of the citizens will continue to be prioritized, but other sectors must also be moved, especially the economy. In addition to the economy which concerns the livelihood of many people, the education sector is also gradually making a transition process by opening some schools and conducting face-to-face learning models in the classroom, intended for schools located in the green zone. The Covid-19 pandemic has an impact on the world of education, the corona virus outbreak has hampered teaching and learning activities which usually take place face-to-face. Even so, this pandemic was able to accelerate education 4.0. The learning system is carried out remotely by utilizing information technology.